Avaliação da ação de estabilizantes anti-UV no desempenho de compósitos de polipropileno, reforçados com fibras de coco, submetidos a diferentes técnicas de envelhecimento artificial - Staffa, Lucas Henrique (Universidade Federal de São Carlos, 2016)
Currently, there has been a search for economically viable and sustainable products in various market segments. Lighter materials that can be recycled have become a strategic issue for many industries. In this sense, the utilization of lignocellulosic fibers in polymeric composites, are becoming increasingly viable as substitutes for inorganic minerals reinforcements, mainly glass fibers. In this study, polypropylene (PP) natural composites reinforced with coir fiber (CF), compatibilized with maleic anhydride grafted polypropylene (PPMAH) and stabilized with a hindered amine (Tinuvin® 791) and UV absorber (Hostavin® ARO 8), were prepared via extrusion. The effect of the additives and their interactions and the influence of 1000 hours exposure in two types of accelerated weathering (Ultraviolet B and xenon arc) in the PP/CF composites were analyzed by mechanical properties (tensile properties), scanning electron microscopy (SEM), differential Scanning Calorimetry (DSC) and colorimetry. The results indicate that the incorporation of coir fiber, in the presence of the compatibilizer, significantly increases tensile strength, but in the absence of the compatibilizer, the coir fiber act as stress concentrators, allowing a lower tensile strength to the sample.The joint presence of Tinuvin® and the compatibilizer has a negative effect on tensile strength and on the compatibility of the natural fiber with the matrix. UV absorber did not affect the compatibility of the PP/CF composites. Post-weathering results indicate that UVB caused more intense degradation than xenon arc. However, decreasing Tinuvin® efficiency evidence were not possible to be confirmed. Through electron micrographs, DSC analysys and tensile tests, it is noted the additive system based on (Tinuvin®+ Hostavin®) as the most effective protection system against the artificial weathering.
Evaluation of anti-uv stabilizers action in coir fiber reinforced polypropylene composites performance, submitted to different techniques artificial weathering
Keywords: Compósitos naturais; Fibra de coco; Polipropileno; Estabilizantes; Compatibilização; Natural composites; Coir fiber; Polypropylene; Photostabilizers; Compatibilization; Artificial weathering; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA